The impact of a significant weight loss on inflammation assessed on DCE-MRI and static MRI in knee osteoarthritis: a prospective cohort study. Issue 6 (June 2020) - Daugaard, C.L.; Henriksen, M.; Riis, R.G.C.; Bandak, E.; Nybing, J.D.; Hangaard, S.; Bliddal, H.; Boesen, M.
Summary: Objective: To study the impact of weight loss on inflammation in individuals with overweight and knee osteoarthritis (OA) using both static- and dynamic contrast-enhanced (DCE)-MRI and assess the association of these changes to pain. Design: Individuals with overweight (BMI > 27) and knee OA were examined before and after a >5% weight loss over 8 weeks (ClinicalTrials.gov NCT02905864). Using 3-T MRI, inflammation was quantified from non-contrast enhanced static-MRI according to MOAKS and contrast enhanced static MRI according to BLOKS and 11-point whole-knee synovitis score. DCE-MRI was used to assess the inflammation in the infra patellar fat pad (IPFP). Pain was assessed using KOOS. Results: Complete data were available in 117 participants with a mean age of 60 years, BMI of 35 kg/m 2 and KOOS pain score of 64. Mean weight loss was 12 kg and KOOS pain was improved by 13 points at follow-up. Change in inflammation was not associated with weight loss in static MRI. None of the MRI variables correlated with the change in KOOS pain. Conclusion: Weight loss did not induce a significant change in inflammation in individuals with overweight and OA. The significant clinical beneficial effect of weight loss on knee pain in individuals with overweight and knee OA seems uncoupled to changes in imaging markers of synovitis.